Made for the job or by the job? A lab-in-the-field experiment with firefighters - Ondřej Krčál; Rostislav Staněk; Martin Slanicay (Masaryk University, Faculty of Economics and Administration, 2019)
A large body of evidence supports a negative association between risk aversion of workers and the level of risk they face in their occupations. This relationship could be explained by the self-selection of workers into jobs according to their risk preferences or by the effect on risk attitudes of occupations in which people face or witness dangerous situations. We use incentivized experiments to measure risk preferences among three different groups: experienced firefighters, novice firefighters, and students. We find that experienced firefighters are less risk-averse than novice firefighters, and these in turn are less risk-averse than students. The effects remain significant even after controlling for other relevant differences between these groups. Our findings suggest that the observed relationship between risk aversion and high-risk occupations is not only a result of self-selection but also of people's preferences being shaped by their work lives.
Keywords: 330; risk preferences; high-risk occupations; self-selection; lab-in-the-field experiment